Neutral Point Voltage of Electric Motor for Multilevel Drive in Electric Vehicle - Dubey, Rishav; Kannan, Varun Prasath (My University, 2024)
Abstract As electric vehicles (EVs) continue to gain traction as a sustainable transportation solution, the demand for efficient and reliable electric motor drives intensifies. The major components affecting these are inverters, motors, batteries, and the control system. Here we are working on inverters and the machine. Usually, in an Electric Vehicle, a high-frequency current is drawn by the electric machine from the inverter which causes conducted emissions. In this thesis, common-mode current and voltage at the AC side of a two-level inverter and a three-level neutral point clamped inverter that are coupled to the electrical machine are estimated . This thesis also analyses the effect on the voltage at different modulation index and different load conditions. A common-mode noise filter at the inputs of the two inverters was added to check the effect of the filter on the output and validate the flow of the common mode current. Utilizing simulation tools like PLECS and LTSpice and experimental values of the electric machine, the High-Frequency current is determined in the frequency domain. Overall, this study contributes to the advancement of neutral point voltage inverters in multilevel electric motor drives, offering valuable insights and practical solutions to optimize the performance of electric vehicles in terms of efficiency, reliability, and environmental sustainability.
Keywords: Keywords: Common-mode, modulation index, frequency